Ghost Writing and Plagiarism - Muhammad Khurram, Muhammad Khurram (Students’ Supplement of Journal of Rawalpindi Medical College, 2019)
Ghost writing means that an individual write for another person who is considered to have written these.2 It is also called contract cheating. Anything especially autobiographies, books, assignments, articles, and speeches can be ghost written. Why someone opt for ghost writing is interesting. Some get it as they don’t have time because of busy schedules, others consider that although their narrative is important and interesting but they do not have sufficient time to write or what they will write will not be impressive or up to mark. Economic gain, job and friendship are common reasons for which a ghost writer allows other to take credit of his work. As everywhere, ghost writing culture is also there in Pakistani scenario. Speeches of politicians and government officials are written by persons who may be hired or are employed in the concerned department. It has been said that biographies of two of the former Pakistani heads of state were written by ghost writers.3